Trends in basic diploma nursing programs within the provincial systems of education in Canada, 1964 to 1974. - Létourneau, Marguerite. (University of Ottawa (Canada), 1975)
The purpose of this study was to identify trends in basic diploma nursing programs at the post-secondary level within the provincial systems of education. The first move to the system of education having been initiated in 1964, this study was primarily concerned with the past decade. Areas of research were: forces at the root of the transfer of programs; structural organization and policies governing programs; curricula; students and faculty. Following an overview of diploma nursing education from its inception in 1874, the report presents an analysis of diploma nursing programs in the various provincial settings. The final chapter consists of a comparative analysis of forces, characteristics of programs and trends on a nation-wide basis. Findings indicated that the trend away from hospital-oriented and toward college-centered programs has permeated Canadian diploma nursing education. The process was found to be complete in Saskatchewan, Ontario and Quebec; partial in British Columbia, Alberta and Manitoba; in the Atlantic provinces, it is non-existent but trends point to future changes. Forces at the root of changes were political, economic, social and technical. Forces which tended to promote innovation likewise tended to inhibit change. Evidence points to lines of direction that subsequent events will tend to follow. A first movement is the continued development of nursing programs within the systems of education. The trend spells the demise of a century-old system and the continued growth of a new pattern. A second trend is the continued development of programs in a manner akin to other similar college programs. The move is toward a uni-jurisdictional form of control, programs being subject to the scrutiny of authorized Departments of Education. Nurses associations will progressively lose control over diploma programs, and become exclusively regulatory bodies. A form of national accreditation will become the accepted body for the evaluation of programs across Canada. Licensure examinations will continue to serve as a useful measure in the selection of qualified members, but the trend is away from the present medical model and toward an integrated or nursing model. A third trend is an increased effort to clarify the focus of programs in the light of existing health needs. The present ill-defined dissatisfaction with the product of diploma programs will require clarification. A fourth trend reflects a balance between general and nursing education, although finding adequate learning experiences for students is increasingly problematic. A final trend is the continued penury of qualified faculty members. It is yet too early to determine the outcome of changes which occurred in the past decade, but results clearly demonstrated that the trend toward college-centered programs can no longer be viewed as the result of a fad; rather it was regarded as a process rapidly becoming a fact. The study made no attempt to evaluate or to make value judgments with regard to the new pattern of diploma nursing education in Canada, but suggestions for further research emerged.
Keywords: Health Sciences, Nursing.